Socialisation entre pairs et genre lors du passage en 6e - Benoit Dejaiffe; Gaelle Espinosa (Éducation et Socialisation)
The objective of this paper is to contribute to the understanding of the peer socialization process of students during the transition between primary and secondary school, as the entry into secondary school, which becomes part of the students’ school experience, requires of them that they develop new social skills. Does this peer socialization process take place in the same way for girls and boys? The research is anchored in a comprehensive paradigm, and the methodology used consists of two series of semi-structured interviews conducted with 25 students, one series conducted at the end of their last year in primary school and the other one at the end of their first year in secondary school. The results show that beyond the stereotyped discourse held by the students according to which boys and girls experience their entry into secondary school in the same manner, a more detailed analysis reveals that there is a difference in the way girls and boys talk about their own experience in terms of peer socialization and in the words they use to formulate it.